Vocational Rehabilitation Services A Consumer Guide for Postsecondary Students - Colley, Debra; Gingerich, Jade; American Council on Education, Washington, DC. HEATH Resource Center ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
This guide assists individuals with disabilities to understand vocational rehabilitation (VR) services available to postsecondary students. Presented in a question-and-answer format, the guide covers the following topics: purpose of vocational rehabilitation, eligibility of postsecondary students, implications of geographical relocation, attendance at out-of-state programs, variations in financial support among states, the appeal process, VR eligibility criteria and postsecondary programs, the application process, locating the local VR office, development of the Individual Written Rehabilitation Plan, medical examination requirements, services provided by the VR program, coordination between the VR program and the high school/college transition program, college services provided by the VR program, payment for VR services, sources of additional financial aid, limitations on VR services for students desiring graduate or second bachelor's degrees, independent living services, and termination of postsecondary rehabilitation services. (DB)
Availability: HEATH Resource Center, One Dupont Circle, Suite 800, Washington, DC 20036-1193 (single copy free).
Sponsoring Agency: Department of Education, Washington, DC.
Contract Number: H030C002-95.
ERIC Note: For earlier edition, see ED 332 404.
Students.
May also be available online. Address as at 14/8/18
Keywords: Disabilities; Eligibility; Higher Education; Postsecondary Education; State Programs; Vocational Rehabilitation; Guides, Non-Classroom.